Agriculture and tourism in Serbia - Gulan, Branislav; Stanković, Vojislav (Economics of Agriculture, 2010)
In Serbia on the area of 4. 1 million hectares of arable agricultural land from 15 to 20 million t of agrarian produce has been produced annually in the value of near 5. 5 billion dollars. In 2009 the food export amounted to 1. 94 billion dollars. Higher food production with the development of rural tourism is possible to be realised if in the rural development of Serbia would be invested 1. 5 billion dollars and the region would be made known the territory without the GMOs. It is of extreme importance since 10 percent of the inhabitants in the EU or 50 million of them are for this kind of food. Thus Serbia might double its food production for three years now and its value would be seven billion dollars and in 2030 the export value would be nine billion dollars. The agriculture and tourism in Serbia are not strategic economic branches. If it would have been invested in the agriculture Serbian villages would have stopped disappearing since one fourth of near 4 600 of them is on this path.